Scandinavian Museums and Cultural Diversity (Museums and Diversity, 2008)
Museums face the task of representing the similarities and differences that exist between groups, such as national identities and indigenous and minority voices, material and intangible heritage, and current status and past history. In order to achieve this aim, a complex and not always easily compatible set of interests have to be taken into account, from those of the museum itself, to those of its main audiences, sources of support, and the groups that are, or wish to be, represented. The approach taken by Scandinavian museums in response to this challenge highlights a very active concern for forms of cultural diversity and how they are interrelated. By bringing together debates and discussions of diversity, this volume offers insight into the Nordic region and its diverse peoples, from the Sámi and the Inuit to newer immigrants. It presents a set of historical reviews on the formation of national museums and emerging and contested perceptions of national identity. Furthering the general debate on representations of diversity and museums, it also offers museum curators possible ways forward